Aktivitas Antibakteri Gel Ekstrak Daun Kelengkeng (Dimocarpus Longan L.) Terhadap Pertumbuhan Bakteri Staphylococcus Aureus dengan Metode Difusi Sumuran - Anggi Lisa Talia; Riana Putri Rahmawati; Istianatus Sunnah (KOLONI, 2026)
Longan leaves (Dimocarpus longan L.) contain secondary metabolite compounds flavonoids, tannins, saponins, alkaloids that can be used as antibacterials in making gel preparations. Longan leaf extract gel preparations can be used as a substitute for gel preparations with excess conventional ingredients, safe for the skin and long-term use. The purpose of this study was to analyze the antibacterial activity of longan leaf extract gel preparations against Staphylococcus aureus. Longan leaf extract was extracted using 96% ethanol solvent by Ultrasound Assisted Extraction (UAE) method at 40 ℃ for 20 minutes. Qualitative testing of metabolite compounds includes flavonoids, tannins, saponins and alkaloids. Longan leaf extract gel preparations were formulated with concentrations of F1 (2%), F2 (4%), F3 (6%). Antibacterial activity was tested using the well diffusion method by forming wells on the surface of the agar medium. The data obtained were analyzed using the One-Way ANOVA test to obtain the average value and showed significant differences. The results of the longan leaf extract gel preparation formulation study showed that the physical quality of the preparation met the requirements. In the antibacterial activity test of the gel preparation, the inhibition zone value F0 was found to be no inhibition zone; F1 (2%) 6.56 ± 1.338 mm (moderate); F2 (4%) 8.45 ± 1.131 mm (moderate); F3 (6%) 9.29 ± 1.130 mm (moderate); positive control gel clindamycin phosphate 1% 26.73 ± 0.335 mm (very strong) and negative control distilled water had no inhibition zone. Based on the results of the study, it can be concluded that longan leaf extract gel has potential as an antibacterial against Staphylococcus aureus which is significantly different (<0.05).